Biosynthesis and tissue-specific partitioning of camphor and eugenol in Ocimum kilimandscharicum - Singh, Priyanka; Kalunke, Raviraj M.; Shukla, Anurag; Tzfadia, Oren; Thulasiram, V. Hirekodathakallu; Giri, Ashok P. (Phytochemistry, 2020)
In Ocimum kilimandscharicum, the relative volatile composition of camphor in leaves was as high as 55%, while that of eugenol in roots was 57%. These metabolites were differentially partitioned between the aerial and root tissues. Global metabolomics revealed tissue-specific biochemical specialization, evident by the differential distribution of 2588 putative metabolites across nine tissues. Next-generation sequencing analysis indicated differential expression of 51 phenylpropanoid and 55 terpenoid pathway genes in aerial and root tissues. By integrating metabolomics with transcriptomics, the camphor biosynthesis pathway in O. kilimandscharicum was elucidated. In planta bioassays revealed the role of geranyl diphosphate synthase (gpps) and borneol dehydrogenase (bdh) in camphor biosynthesis. Further, the partitioning of camphor was attributed to tissue-specific gene expression of both the pathway entry point (gpps) and terminal (bdh) enzyme. Unlike camphor, eugenol accumulated more in roots; however, absence of the eugenol synthase gene in roots indicated long distance transport from aerial tissues. In silico co-expression analysis indicated the potential involvement of ATP-binding cassette, multidrug and toxic compound extrusion, and sugar transporters in eugenol transport. Similar partitioning was evident across five other Ocimum species. Overall, our work indicates that metabolite partitioning maybe a finely regulated process, which may have implications on plant growth, development, and defense.
Keywords: Borneol dehydrogenase; Camphor; Eugenol; Geranyl diphosphate synthase; Lamiaceae; Metabolite partitioning; Metabolomics; Ocimum kilimandscharicum; Transcriptomics

Unveiling the cell wall-targeting mechanisms and multifaceted virulence modulation by a eugenol glycoconjugate against aspergillus fumigatus: insights from in vitro and in ovo studies - Gupta, Lovely; Verma, Shalini; Goswami, Lakshmi; Kamboj, Himanshu; Sen, Pooja; Bhattacharya, Asish K.; Vijayaraghavan, Pooja (Journal of Applied Macrobiology, 2024)
Aim The primary objective of this study was to elucidate the putative cell wall-associated targets of compound 6i, a glycoconjugate of eugenol, in Aspergillus fumigatus, while also evaluating its toxicity and assessing histopathologic alterations in the liver, heart, and kidney of compound 6i-treated embryos using an in ovo model.Method To achieve this aim, compound 6i was synthesized, and a series of biochemical assays were performed to determine its impact on the fungal cell wall. Additionally, quantitative real time-PCR and liquid chromatography-mass spectrometry/mass spectrometry analyses were conducted to investigate changes in gene and protein expression profiles associated with melanin biosynthesis, conidiation, siderophore production, transcriptional regulation of beta-glucan biosynthesis, and calcineurin activity in A. fumigatus.Results The experimental findings revealed that compound 6i exhibited notable antifungal activity against A. fumigatus by perturbing cell wall integrity, hindering ergosterol, glucan, and chitin biosynthesis, and inhibiting catalase production. Moreover, relative gene expression and proteomic analyses demonstrated that compound 6i exerted both downregulatory and upregulatory effects on several crucial genes and proteins involved in the aforementioned fungal processes. Furthermore, increased expression of oxidative stress-related proteins was observed in the presence of compound 6i. Notably, the glycoconjugate of eugenol did not elicit cytotoxicity in the liver, heart, and kidney of chick embryos.Conclusion The current investigation elucidated the multifaceted mechanisms by which compound 6i exerts its antifungal effects against A. fumigatus, primarily through targeting cell wall components and signaling pathways. These findings underscore the potential of the eugenol glycoconjugate as a promising antifungal candidate, warranting further exploration and development for combating A. fumigatus infections.
Keywords: Aspergillus fumigatus; cell wall integrity; Eugenol; Glycoconjugate; Transcription regulators; Virulence

Comprehensive in vitro and in silico assessment of eugenol glycoconjugates against azole and amphotericin B resistant Rhizopus spp. - Sen, Pooja; Gupta, Lovely; Chauhan, Aastha; Goswami, Lakshmi; Bhattacharya, Asish K.; Sengupta, Abhishek; Vijayaraghavan, Pooja (Molecular Biology Reports, 2025)
Background Rhizopus spp. is a major cause of mucormycosis, a severe infectious disease with high morbidity and mortality. Treatment is challenging due to rising antifungal resistance. Glycosylation is a crucial technique for enhancing the properties of phenolic compounds like eugenol. The present study aims to examine the antifungal efficacy of eugenol glycoconjugates against azole and amphotericin B-resistant Rhizopus isolates. Methods and results Out of 50 soil samples, 12 isolates belonging to Mucorales were obtained, of which 7 were identified as Rhizopus spp. via 18S ITS sequencing. Antifungal susceptibility testing (AST) revealed that all Rhizopus isolates were resistant to amphotericin B (MIC > 1 mu g/mL). Most isolates also showed resistance towards posaconazole (MIC > 1 mu g/mL) and itraconazole (MIC > 2 mu g/mL). AST of eugenol glycoconjugate (coded 6g) showed efficacy against resistant Rhizopus isolates, with MIC values ranging from 6.25 mu g/mL to 25 mu g/mL. Flow cytometry confirmed its fungicidal activity, correlating with MIC data. Compound 6g significantly reduced conidial germination within 24 h and exhibited no cytotoxicity on A549 lung cancer cells. In-silico analysis revealed a negative binding affinity of compound 6g for the spore coat protein CotH3, which could be a potential antifungal target. Conclusion Compound 6g could be an potential antifungal molecule against resistant Rhizopus spp, which requires further studies.
Keywords: Antifungals; Eugenol; Glycoconjugates; Mucormycosis; Resistance; Virulence